Analysis of Global Tourism and Creative Economy Trends to Support Jakarta as a Global City - Haidlir, Banu Muhammad; Musthofa, Budiman Mahmud; Mukhlish, Basuki Muhammad (UI Scholars Hub, 2024)
The city of Jakarta is currently faced with new challenges to become a global city because the status of the country's capital has been revoked. The transformation of Jakarta into a global city requires in-depth study by exploring global trends and looking for the city's potential so that Jakarta can become a globally competitive city. One of the areas that is the focus of this study is tourism and the creative economy. The aim of this study is to analyze global and national trends in tourism and the creative economy. Through library research and document study methods, the author discovered various trends in tourism and the global creative economy. The results of the study show that throughout 2023-2024 there will be many trends in the tourism and creative economy sectors, such as the smart tourism trend, sustainable tourism, digital tourism, as well as the very large growth trend in the creative economy sector at the national and international levels. The various global trends in tourism and the creative economy that were discovered were then analyzed by examining the relationship between the trends and the potential of various resources that Jakarta has. It is hoped that the results of this study can become one of the initial studies on the development of tourism and the creative economy in Jakarta to become a city that is able to compete with other global cities in the world.